Auti-Jector / Nur Syuhada Muhammad … [et al.] - Muhammad, Nur Syuhada; Ibrahim, Asiah; Asmuni, Mohd Sharul Shafik; Johari, Nurul Filza Irdina; Moktar, Muhammad Fadhil; Mohd Rohari, Mohd Sharizami (Division of Research and Industry Linkages, 2017)
Autism is a non-physical retarded but it is actually a symptoms spectrum disorder for kids that affect their communication, social interaction, and also behavior. They are unusually intense or focused interests because they cannot pay attention on something for a long period of time and their interest keeps on changing according to their moods. Moreover, they have also their own characteristics which are other people cannot copy their specialization. Other than that, they also do not respond to too many of the non-verbal forms of communication with other people and do not know how to express their emotions, eye contact, physical gestures and also facial expressions. So, we come out with the new idea on how we can trigger their sensory interest by playing with many aspects such as on touch, visual and sound. We have innovated one o f the existing Autism products that called "Auti-Jector" that would be able to play an important role to help autism people to trigger their sensory responsiveness. As we know, they will put more interest on something that can give trigger their attention to react to their sensory. Therefore, Auti-Jector is a projector that made special for autism kids that enable them to respond with the sounds, visual and touch. The benefits of this kind of innovation are not only help kids to recognize each of the element’s, in fact it will also help their parents on how to teach their kids by organizing each of the items in the Auti-jector. By providing this kind of innovation product, we will ensure that autism kids will be more organized, as well as their sensory receptors will be better